PERANCANGAN 3D PROPERTI MAKANAN UNTUK KEPERLUAN LOOK DEVELOPMENT EFEK VISUAL PADA FILM PENDEK “MIE MEDAN” - Matheus Prayogo; Christian Aditya (Universitas Multimedia Nusantara, 2019)
Visual Effect can be used to enhance storytelling in the filmmaking process. The Visual Effects technology itself already has grown to become faster and better in production. However, in the Visual Effects Department, the artist needs digital props to show what’s on the screen. Therefore, this study seeks to create props for Visual Effects needs. This present study describes how to create believable props for visual effects needs in a short film called “Mie Medan”. It concludes that to create a visual effect props, we have to consider to create real-scale and proportion in each set and props to gain believability in film, the hue, and saturation of the color and texture itself will gain more realistic and sense of flavor to the film.